АДАПТИВНА ПРОТИАВАРІЙНА АВТОМАТИКА ЗАБЕЗПЕЧЕННЯ СТАТИЧНОЇ СТІЙКОСТІ ЕНЕРГОСИСТЕМИ - Стогній , Б.С.; Авраменко , В.М.; Сопель , М.Ф.; Прихно , В.Л. (Інститут електродинаміки НАН України, Київ, 2014)
An adaptive emergency control automatics is proposed for maintenance of power systems stability, which is based on microprocessors (MP) and controls the stability margin of the current state and determines the control actions, which are necessary to meet normative requirements as to the active power in the cross sections and so to the voltage at the centers of consumption. Demands to MP emergency control system with centralized formation of dosage control actions are formed. References 6.